The berenstain bears and the bad dream - Berenstain, Jan (U.S.A : Berenstain inc, 1988)
After viewing a scary movie about the space Grizzlies, Brother bear has a nightmare.
Keywords: Nightmares -- fiction; Fear -- Fiction